DECEMBER ACTIVITY REPORT - MARCUS, RICHARD (Tufts Archival Research Center, 2007)
Confidential; Marginalia; Memorandum from Richard Marcus to Martin Gleason regarding December 1989 activities. Lists activities including legislation involving cigarette tax, pubic smoking, media tours, advertising and social cost. Mentions coalitions with labor and their help on indoor air quality issues.